Positive electrode active material and preparation method and application thereof
By using Na4Fex(PO4)2MyP2O7 matrix material and coated with nitrogen-doped carbon and carbon materials, a composite positive electrode active material is formed, and the conductivity and volume expansion problems of NFPP materials are solved, which significantly improves the magnification and cycling performance of sodium ion batteries.
Patent Information
- Application Number
- CN202411975106.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
The electron conductivity and ion mobility of NFPP positive electrode materials have poor electronic conductivity and poor rate performance, and the volume expansion is large during charging and discharging, affecting the cycling performance of the battery.
By using Na4Fex(PO4)2MyP2O7 as the matrix material, and using a nitrogen-doped carbon material as the first cladding layer and a carbon material as the second cladding layer, a positive electrode active material of secondary particles formed by the agglomeration of primary particles is formed. This material improves battery rate performance and cycle stability by improving electrical conductivity and reducing volume expansion.
The conductivity and volume expansion capability of the positive electrode material are significantly improved, thereby improving the rate performance and cycling performance of sodium ion batteries.
Smart Images

Figure CN119786565A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries and relates to a positive electrode active material, in particular to a positive electrode active material and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries have been widely studied and paid attention to in the field of energy storage due to their abundant resources, low price, safety, environmental protection, and excellent performance. Among them, iron-based composite phosphate (NFPP) polyanion materials with high theoretical specific capacity, low volume expansion (<4%), and high structural stability are considered to be one of the most promising sodium cathode materials. However, the inherent electronic conductivity and ion mobility of NFPP materials are poor, resulting in poor rate performance.
[0003] Currently, the conductivity of the positive electrode is mainly improved by carbon coating, but the coating uniformity is generally poor, which affects the conductivity of the material. In addition, during the charge and discharge process of the positive electrode material, lithium ions are released and embedded, causing changes in its crystal structure and volume expansion, which will affect the cycle performance and rate performance of the battery.
[0004] Therefore, it is necessary to improve the conductivity and volume expansion of NFPP positive electrode materials to enhance the cycle performance and rate performance of the battery. Summary of the invention
[0005] In view of the above-mentioned defects, the present invention provides a positive electrode active material, which has high conductivity and small volume expansion during the charge and discharge process, and can effectively improve the cycle performance and rate performance of the battery.
[0006] The present invention also provides a method for preparing the positive electrode active material. The positive electrode active material prepared by the preparation method can effectively improve the cycle performance and rate performance of the battery.
[0007] The present invention also provides a positive electrode sheet, which comprises the positive electrode active material or the positive electrode active material prepared by the preparation method. The positive electrode sheet can be used in a sodium ion battery to effectively improve the cycle performance and rate performance of the battery.
[0008] The present invention also provides a sodium ion battery. Since the battery comprises the above-mentioned positive electrode active material, or the positive electrode active material prepared by the above-mentioned preparation method, or the above-mentioned positive electrode sheet, the battery has good cycle performance and rate performance.
[0009] A first aspect of the present invention provides a positive electrode active material, the positive electrode active material comprising secondary particles formed by agglomeration of primary particles; the primary particles comprising a matrix and a first coating layer coated on the surface of the matrix, and the surface of the secondary particles is coated with a second coating layer;
[0010] The matrix material comprises a chemical composition of Na4Fe x (PO4)2M y P2O7 material; wherein 2.7≤x≤3, x+y=3; M includes at least one of Mn, Mg, Al, Cr, Ti, Co, Cu, Ni, K, and Li;
[0011] The first coating layer includes a nitrogen-doped carbon material, and the second coating layer includes a carbon material.
[0012] The positive electrode active material as described above, wherein the nitrogen-doped carbon material is obtained by sintering a carbon source including nitrogen at a temperature of 200 to 400° C. for 4 to 6 hours.
[0013] The positive electrode active material as described above, wherein the porosity of the positive electrode active material is 10-15%, and / or the powder compaction density of the positive electrode active material is 1.9-2.2 g / cm 3 .
[0014] The positive electrode active material as described above, wherein the mass percentage of the first coating layer in the positive electrode active material is 0.8-1.0 wt %, and / or the mass percentage of the second coating layer is 1.2-1.6 wt %.
[0015] The positive electrode active material as described above, wherein the average particle size of the primary particles is 0.4 to 1.0 μm, and / or the median particle size D50 of the secondary particles is 9 to 11 μm.
[0016] The second aspect of the present invention provides a method for preparing the positive electrode active material of the first aspect, comprising the following steps:
[0017] 1) subjecting raw materials including a sodium source, an iron source, a phosphorus source and a first carbon source to a first sand grinding process, a first granulation process, a crushing process and a first sintering process to obtain a sintered material, wherein the first sintering temperature is 200 to 400° C. and the holding time is 4 to 6 hours; wherein the first carbon source includes nitrogen;
[0018] 2) subjecting the raw materials including the sintering material and the second carbon source to a second sand milling treatment and a second granulation treatment in sequence, and then subjecting the raw materials to a second sintering treatment to obtain a positive electrode active material; wherein the second sintering temperature is 500 to 700° C., and the heat preservation time is 10 to 16 hours.
[0019] The method for preparing the positive electrode active material as described above, wherein in step 1), the median particle size D50 of the raw material after grinding is 150 to 250 nm;
[0020] And / or, step 1) further comprises: obtaining a crushed material after the crushing treatment, wherein the median particle size D50 of the crushed material is 2.7 to 3.5 μm.
[0021] The method for preparing the positive electrode active material as described above, wherein the first sand milling treatment and / or the second sand milling treatment comprises coarse grinding and fine grinding of the raw material;
[0022] The grinding beads in the coarse grinding have a particle size of 0.6 to 0.8 μm, a rotation speed of 1400 to 1700 r / min, and a time of 30 to 80 min;
[0023] The particle size of the grinding beads in the fine grinding is 0.3-0.4 μm, the rotation speed is 1600-2000 r / min, and the time is 120-200 min.
[0024] A third aspect of the present invention provides a positive electrode sheet, comprising the positive electrode active material of the first aspect, or the positive electrode active material prepared by the preparation method of the second aspect.
[0025] The present invention also provides a sodium ion battery, comprising the positive electrode active material of the first aspect, or the positive electrode active material prepared by the preparation method of the second aspect, or the positive electrode sheet of the third aspect.
[0026] The positive electrode active material of the present invention comprises secondary particles formed by agglomeration of primary particles, wherein the primary particles comprise a matrix and a first coating layer coated on the surface of the matrix, and the surface of the secondary particles is coated with a second coating layer, wherein the matrix comprises a chemical composition of Na4Fe x (PO4)2M y The material of P2O7 (2.7≤x≤3, x+y=3), the first coating layer includes nitrogen-doped carbon material, and the second coating layer includes carbon material, to effectively improve the conductivity of the positive electrode material and reduce the volume expansion of the positive electrode active material during the charge and discharge process, thereby improving the rate performance and cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a SEM image of the positive electrode active material in Example 1 of the present invention;
[0028] Figure 2 This is a SEM image of the positive electrode active material in Comparative Example 6 of the present invention;
[0029] Figure 3 10C / 0.2C capacity retention rate curve of the sodium ion battery in Examples 1 to 3 of the present invention and Comparative Examples 1 and 2;
[0030] Figure 4 The Raman spectra of the sintered material in Example 1 of the present invention and the sintered material in Comparative Example 1;
[0031] Figure 5 This is an EDS scan of the positive electrode active material in Example 1 of the present invention;
[0032] Figure 6 This is a distribution diagram of the N element in the EDS scan of the positive electrode active material in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] A first aspect of the present invention provides a positive electrode active material, the positive electrode active material comprising secondary particles formed by agglomeration of primary particles; the primary particles comprising a matrix and a first coating layer coated on the surface of the matrix, and the surface of the secondary particles is coated with a second coating layer;
[0035] The matrix includes a chemical composition of Na4Fe x (PO4)2M y P2O7 material; wherein 2.7≤x≤3, x+y=3; M includes at least one of Mn, Mg, Al, Cr, Ti, Co, Cu, Ni, K, and Li;
[0036] The first coating layer includes a nitrogen-doped carbon material, and the second coating layer includes a carbon material.
[0037] It should be noted that when M includes multiple specific elements among the aforementioned elements, the present invention does not specifically limit the molar ratio between the specific elements.
[0038] The positive electrode active material in the present invention includes secondary particles formed by agglomeration of primary particles, and the primary particles include a matrix and a first coating layer coated on the surface of the matrix, and the surface of the secondary particles is coated with a second coating layer, wherein the first coating layer includes a nitrogen-doped carbon material, and the carbon material doped with non-metallic atoms can effectively improve the ion and electron transmission capacity of the positive electrode active material, thereby improving the rate performance of the battery; however, the first coating layer has a poor coating effect, resulting in the inability to effectively isolate the primary particles during the reaction process, which will cause the primary particles to fuse and agglomerate with each other, and have a negative impact on the cycle performance of the battery. By coating the second coating layer on the outer surface of the first coating layer, or the outer surface of the first coating layer and the matrix, the surface of the matrix not coated with the first coating layer can be filled, and the integrity of the coating layer can be improved, thereby avoiding the fusion and agglomeration of the primary particles, so as to improve the cycle performance of the battery. At the same time, during the charge and discharge process, the positive electrode material often changes its crystal structure due to the release of lithium ions, causing volume expansion, and the second coating layer can act as a buffer layer to relieve expansion stress and reduce the structural damage of the positive electrode material caused by volume expansion, thereby effectively improving the cycle stability of the battery; and the second coating layer can also form an excellent conductive network to further improve the conductivity of the material; therefore, the positive electrode active material can comprehensively improve the rate performance and cycle performance of the battery.
[0039] In addition, due to the high conductivity of the positive electrode active material, the interface impedance can be effectively reduced and the first coulomb efficiency can be improved; and since the matrix includes a chemical composition of Na4Fe x (PO4)2M y The material of P2O7, where 2.7≤x≤3, x+y=3, exhibits an iron-deficient phase because it can effectively improve the sodium ion migration efficiency of the positive electrode active material, thereby further improving the charge and discharge performance of the sodium ion battery.
[0040] In a specific embodiment, the nitrogen-doped carbon material is obtained by sintering a carbon source including nitrogen at a temperature of 200 to 400° C. for 4 to 6 hours.
[0041] Wherein, the carbon source refers to a raw material that provides carbon elements; the carbon source of the present invention is not specifically limited, and only needs to contain nitrogen elements. Exemplarily, the carbon source including nitrogen elements can be selected from at least one of urea, pyrrole, polyacrylonitrile, polyvinyl pyrrolidone (PVP), and polyvinyl alcohol (PVA).
[0042] In a specific embodiment, the porosity of the positive electrode active material is 10-15%. Within this range, the interior of the positive electrode active material particles is relatively compact and dense, which can effectively shorten the diffusion distance of sodium ions in the material, thereby improving the kinetics of the material and further improving the rate performance of the battery.
[0043] Illustratively, the porosity of the positive electrode active material is 10%, 11%, 12%, 13%, 14% or 15%.
[0044] The "porosity" in the present invention is determined by performing SEM testing on the cross-section of the positive electrode active material particles and analyzing the cross-section SEM using MetisVision 1.8256 software. The porosity is the percentage of the area of pores in the cross-section to the total cross-section area.
[0045] In one embodiment, the powder compaction density of the positive electrode active material is 1.9 to 2.2 g / cm 3 Within this range, the powder compaction density of the positive electrode active material is relatively suitable, which not only makes the battery have a higher energy density, but also does not cause excessive compression of the positive electrode material due to excessive compaction density, which reduces the contact area between the active materials and affects the battery capacity, nor does it reduce the wettability of the electrolyte and affect the battery performance.
[0046] For example, the powder compaction density of the positive electrode active material is 1.9 g / cm 3 , 1.95g / cm 3 , 2.0g / cm 3 , 2.05g / cm 3 , 2.1g / cm 3 , 2.15g / cm 3 or 2.2g / cm 3 .
[0047] The "powder compaction density" in the present invention is obtained by testing with a powder compaction tester, and the test pressure is 3T (222.0Mpa).
[0048] In a specific embodiment, the mass percentage of the first coating layer in the positive electrode active material is 0.8-1.0 wt %. Within this range, not only a good coating effect can be achieved, but also the capacity will not be greatly affected.
[0049] Illustratively, the mass percentage of the first coating layer in the positive electrode active material is 0.8 wt %, 0.85 wt %, 0.9 wt %, 0.95 wt % or 1.0 wt %.
[0050] The mass content of the first coating layer in the positive electrode active material of the present invention can be measured by a carbon-nitrogen element analyzer.
[0051] In a specific embodiment, the mass percentage of the second coating layer in the positive electrode active material is 1.2-1.6wt%, which can not only ensure the integrity of the coating, but also not greatly affect the powder compaction density of the positive electrode active material due to excessive coating, thereby ensuring the high energy density of the battery.
[0052] The mass content of the second coating layer in the positive electrode active material in the present invention can be obtained by testing with a carbon-sulfur analyzer.
[0053] Illustratively, the mass percentage of the second coating layer in the positive electrode active material is 1.2 wt%, 1.25 wt%, 1.3 wt%, 1.35 wt%, 1.4 wt%, 1.45 wt%, 1.5 wt%, 1.55 wt% or 1.6 wt%.
[0054] In a specific embodiment, the average particle size of the primary particles is 0.4-1.0 μm. Within this range, the capacity of the positive electrode active material will not be negatively affected.
[0055] Illustratively, the average particle size of the primary particles is 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1.0 μm.
[0056] The average particle size of the primary particles in the present invention can be measured by Nano Measurer software.
[0057] In a specific embodiment, the median particle size D50 of the secondary particles is 9 to 11 μm. Within this range, the gap size between the secondary particles can be reduced to a certain extent, ensuring a higher compaction density, thereby effectively improving the energy density of the battery.
[0058] Illustratively, the median particle size D50 of the secondary particles is 9 μm, 9.5 μm, 10 μm, 10.5 μm or 11 μm.
[0059] The median particle size of the secondary particles in the present invention can be measured by a Malvern particle size laser instrument.
[0060] The second aspect of the present invention provides a method for preparing the positive electrode active material of the first aspect, comprising the following steps:
[0061] 1) subjecting raw materials including a sodium source, an iron source, a phosphorus source and a first carbon source to a first sand grinding process, a first granulation process, a crushing process and a first sintering process to obtain a sintered material, wherein the first sintering temperature is 200 to 400° C. and the holding time is 4 to 6 hours; wherein the first carbon source includes nitrogen;
[0062] 2) The raw materials including the sintering material and the second carbon source are sequentially subjected to a second sand milling treatment and a second granulation treatment, and then subjected to a second sintering to obtain a positive electrode active material; wherein the second sintering temperature is 500-700° C., and the heat preservation time is 10-16 hours.
[0063] Specifically, in step 1), the raw materials including a sodium source, an iron source, a phosphorus source and a first carbon source are sequentially subjected to a first sand grinding treatment, a first granulation treatment and a crushing treatment, and then the crushed material obtained after the crushing treatment is subjected to a first sintering, and the sintering temperature is controlled to be 200-400°C, and the insulation time is 4-6h to obtain a sintered material.
[0064] Illustratively, the sintering temperature is 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C or 400°C; and the sintering time is 4h, 5h or 6h.
[0065] The present invention does not specifically limit the heating rate in the first sintering, and a suitable heating rate can be selected according to actual conditions; for example, the heating rate is 2 to 5° C. / min.
[0066] The sodium source in the present invention refers to the raw material providing the sodium element, the iron source refers to the raw material providing the iron element, the phosphorus source refers to the raw material providing the phosphorus element, and the first carbon source refers to the raw material providing the carbon element and the nitrogen element, as long as it contains the target element (sodium, iron, phosphorus, carbon, nitrogen), all belong to the limitation of the present invention. It should be explained that when the raw material includes two or more elements in the target element at the same time, the raw material can be understood as the element source of two target elements. For example, when the raw material is ferric phosphate, it acts as an iron source and a phosphorus source at the same time.
[0067] Exemplarily, the sodium source includes at least one of sodium phosphate, sodium pyrophosphate, trisodium monohydrogen pyrophosphate, and disodium dihydrogen pyrophosphate; the iron source includes at least one of ferric nitrate, ferric citrate, ferric sulfate, ferric phosphate, and ferric oxide; the phosphorus source includes at least one of phosphoric acid, phosphate, and pyrophosphate; and the first carbon source includes at least one of urea, pyrrole, polyacrylonitrile, polyvinyl pyrrolidone (PVP), and polyvinyl alcohol (PVA).
[0068] The present invention does not specifically limit the sources of the sodium source, iron source, phosphorus source and the first carbon source. For example, commercially available products or products prepared by conventional preparation methods well known to those skilled in the art may be used.
[0069] The present invention does not specifically limit the molar ratio of the sodium source, the iron source and the phosphorus source, but only requires that the chemical formula of the matrix in the prepared positive electrode active material satisfies Na4Fe x (PO4)2M y P2O7 (2.7≤x≤3, x+y=1), wherein M includes at least one of Mn, Mg, Al, Cr, Ti, Co, Cu, Ni, K, and Li.
[0070] The present invention does not specifically limit the amount of the first carbon source added. Furthermore, the mass percentage of the first coating layer in the positive electrode active material can be further controlled by controlling the amount of the first carbon source added. For example, controlling the amount of nitrogen added to the first carbon source to account for 1% of the Na4Fe x (PO4)2M y The theoretical generation mass of P2O7 (2.7≤x≤3, x+y=1) is 2000-3000 ppm, which helps to make the mass percentage of the first coating layer in the positive electrode active material 0.8-1.0%.
[0071] In the present invention, "Na4Fe x (PO4)2M y The theoretical generation mass of P2O7 (2.7≤x≤3, x+y=3) can be calculated by the following method:
[0072] 1 mol of Na4Fe x (PO4)2M y The theoretical generated mass (g) of P2O7 (2.7≤x≤3, x+y=3) = 4×A1+x×A2+y×A3+4×A4+15×A5, wherein A1 is the molar mass of Na, A2 is the molar mass of Fe, A3 is the molar mass of M element, A4 is the molar mass of P, and A5 is the molar mass of O, and the unit is g / mol; wherein the M element refers to at least one of Mn, Mg, Al, Cr, Ti, Co, Cu, Ni, K, and Li.
[0073] The present invention does not specifically limit the specific conditions of the first sand milling treatment, and it is only necessary to uniformly mix the raw materials including the sodium source, the iron source, the phosphorus source and the first carbon source.
[0074] The present invention does not specifically limit the method of the first granulation treatment. For example, the granulation treatment can be performed by spray drying. Preferably, the inlet temperature in the spray drying is 200-210°C, and the outlet temperature is 90-95°C.
[0075] Illustratively, the inlet temperature is 200°C, 202°C, 204°C, 206°C, 208°C or 210°C and the outlet temperature is 90°C, 91°C, 92°C, 93°C, 94°C or 95°C.
[0076] The present invention does not specifically limit the method of crushing treatment. For example, the crushing treatment can be carried out by air flow crushing, mechanical crushing or ball mill crushing.
[0077] In step 2), the raw materials including the sintering material and the second carbon source are sequentially subjected to a second sand grinding treatment and a second granulation treatment, and the product obtained after the second granulation treatment is subjected to a second sintering, and the second sintering temperature is controlled to be 500-700° C. and the insulation time is 10-16 hours to obtain a positive electrode active material.
[0078] Illustratively, the second sintering temperature is 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, 620°C, 640°C, 660°C, 680°C or 700°C; and the holding time is 10h, 12h, 14h or 16h.
[0079] The second carbon source in the present invention refers to a raw material including carbon elements. Exemplarily, the second carbon source includes at least one of glucose, sucrose, caramel, starch, citric acid, and dextrin.
[0080] The present invention does not specifically limit the source of the second carbon source. For example, a commercially available product or a product prepared by a conventional preparation method well known to those skilled in the art may be used.
[0081] The present invention does not specifically limit the amount of the second carbon source added. Furthermore, the mass percentage of the second coating layer in the positive electrode active material can be further controlled by controlling the amount of the second carbon source added. For example, controlling the amount of the second carbon source added to account for 1% of the Na4Fe x (PO4)2M y P2O7 (2.7≤x≤3, x+y=3) theoretically generates 6-8% of the mass, so that the mass percentage of the second coating layer in the positive electrode active material is 1.2-1.6%.
[0082] The present invention does not specifically limit the second sanding treatment and the second granulation treatment, which can be consistent with the first sanding treatment and the second sanding treatment in step 1), and will not be described in detail here.
[0083] The present invention does not specifically limit the heating rate in the second sintering. For example, the heating rate is 2 to 5° C. / min.
[0084] The preparation method of the positive electrode active material in the present invention first performs a first sand milling treatment on the raw materials including a sodium source, an iron source, a phosphorus source and a first carbon source so that the components can be evenly mixed; then, the product after the grinding treatment is subjected to a first granulation treatment and a first crushing treatment, wherein the first granulation treatment can not only make the distribution of the components in the raw materials more uniform, but also help to improve the structural tightness of the positive electrode active material and improve the packing density of the material; the first crushing treatment is beneficial to further improve the tightness of the material structure, reduce the porosity, and improve the compaction density of the material in the subsequent second granulation treatment; then, the product after the crushing treatment is pre-sintered (i.e., the first sintering) at a specific temperature and time, and the sintering temperature is low and the time is short. Under this condition, the first carbon source is not sufficient to be completely coked and decomposed, and the raw materials are not sufficient to react to form primary particles, which helps the first carbon source to be coated on the surface of the unreacted raw material, plays a certain separation role, and promotes the formation of small-diameter primary particles in the subsequent second sintering. Primary particles with smaller particle sizes can effectively shorten the diffusion path of lithium ions, and the first coating layer coated on their surface contains non-metallic atomic nitrogen, which can effectively improve the ion and electron transmission capacity of the positive electrode active material, thereby improving the battery's rate performance.
[0085] However, in order to avoid excessive N content in the positive electrode active material affecting the capacity, the amount of the first carbon source added during the preparation process should not be too much. Therefore, the first coating layer is often unevenly coated on the surface of the primary particles. This uneven coating will result in the failure to form an effective partition between the primary particles during the secondary sintering process, which will easily cause the primary particles to fuse and agglomerate with each other, have a negative impact on conductivity, increase polarization during the cycle, and reduce cycle performance.
[0086] Therefore, the present invention performs secondary coating, and the coated second coating layer can fill the uncoated part of the first coating layer, improve the integrity of the coating layer, avoid the fusion and agglomeration of the primary particles, and improve the conductivity of the positive electrode active material; in addition, the second coating layer can also alleviate the volume expansion of the positive electrode active material during the charge and discharge process. It should be noted that in the secondary coating process, the sintered material obtained by the first sintering and the second carbon source need to be subjected to a second sand milling treatment, which helps the second carbon source to be evenly distributed in the raw material to form a uniform carbon coating layer; and the product after the second sand milling treatment needs to be subjected to a second granulation treatment, which can effectively improve the uniformity of the particle size of the positive electrode active material, obtain positive electrode active material particles with a compact structure, and improve the packing density of the material.
[0087] Therefore, the positive electrode active material prepared by the above preparation method can effectively improve the cycle performance and rate performance of the battery.
[0088] In a specific embodiment, in step 1), the median particle size D50 of the raw material after the first sand milling treatment is 150-250 nm. Within this range, it is beneficial to improve the powder compaction density of the positive electrode active material.
[0089] Exemplarily, the median particle size D50 of the raw material after the first sand milling treatment is 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm or 250 nm.
[0090] The first sand grinding treatment is not specifically limited in the present invention, and the D50 of the raw material after treatment is only required to be between 150 and 250 nm. In one embodiment, the raw materials including the sodium source, the iron source, the phosphorus source and the first carbon source are mixed with deionized water to obtain a mixed slurry; the mixed slurry is coarsely ground and finely ground in sequence to obtain a grinding material with a median particle size D50 of 150 to 250 nm.
[0091] In a specific embodiment, in step 1), a crushed material is obtained after the crushing treatment, and the median particle size D50 of the crushed material is 2.7 to 3.5 μm. Since the positive electrode active material particles in the present invention are obtained by subjecting the crushed material to a first sintering, a second sand grinding treatment, and a second granulation treatment and then a second sintering, the positive electrode active material particle structure in the present invention is secondary particles formed by the agglomeration of crushed material particles, that is, positive electrode active material particles. When the D50 of the crushed material is within the aforementioned range, it helps to form a gradation between the crushed material particles and improve the compaction density of the material; at the same time, the density of the particle structure after the second granulation treatment will decrease, which can enrich the embedding and escape channels of sodium ions in the crystal lattice, and further improve the rate performance of the positive electrode active material.
[0092] Illustratively, the median particle size D50 of the pulverized material is 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm or 3.5 μm.
[0093] In a specific embodiment, the first sand grinding treatment includes coarse grinding and fine grinding of the raw material; in the coarse grinding, the particle size of the grinding beads is 0.6-0.8 μm, the rotation speed is 1400-1700 r / min, and the time is 30-80 min; in the fine grinding, the particle size of the grinding beads is 0.3-0.4 μm, the rotation speed is 1600-2000 r / min, and the time is 120-200 min.
[0094] In a specific embodiment, the second sand grinding treatment includes coarse grinding and fine grinding of the raw material; in the coarse grinding, the grinding bead particle size is 0.6-0.8 μm, the rotation speed is 1400-1700 r / min, and the time is 30-80 min; in the fine grinding, the grinding bead particle size is 0.3-0.4 μm, the rotation speed is 1600-2000 r / min, and the time is 120-200 min.
[0095] When the first sand milling treatment and the second sand milling treatment are performed in the aforementioned manner, the uniformity of coating of the first carbon source and the second carbon source can be effectively improved, and the rate performance of the positive electrode active material can be further improved.
[0096] Exemplarily, the particle size of the grinding beads in the coarse grinding is 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm or 0.8 μm; the rotation speed of the coarse grinding is 1400 r / min, 1500 r / min, 1600 r / min or 1700 r / min; and the time of the coarse grinding is 30 min, 40 min, 50 min, 60 min, 70 min or 80 min.
[0097] Exemplarily, the particle size of grinding beads in fine grinding is 0.3 μm, 0.32 μm, 0.34 μm, 0.36 μm, 0.38 μm or 0.4 μm; the rotation speed of fine grinding is 1600 r / min, 1700 r / min, 1800 r / min, 1900 r / min, 2000 r / min or; the time of coarse grinding is 120 min, 140 min, 160 min, 180 min or 200 min.
[0098] The third aspect of the present invention provides a positive electrode sheet, comprising the positive electrode active material of the first aspect, or the positive electrode active material prepared by the preparation method of the second aspect. Therefore, the positive electrode sheet can effectively improve the rate performance and cycle stability of the sodium ion battery.
[0099] The fourth aspect of the present invention provides a sodium ion battery, comprising the positive electrode active material of the first aspect, or the positive electrode active material prepared by the preparation method of the second aspect, or the positive electrode sheet of the third aspect. Therefore, the sodium ion battery has a higher rate performance and a longer cycle life.
[0100] Hereinafter, the positive electrode active material of the present invention is described in detail through specific examples.
[0101] Example 1
[0102] 1) adding a mixed raw material of sodium pyrophosphate, iron oxide, iron phosphate, manganese acetate and urea into deionized water to obtain a mixed slurry with a solid content of 25 wt%, wherein the molar ratio of the Na element, Fe element, Mn element and P element in the mixed raw material is 4:2.9:0.1:4, and the amount of nitrogen added in the urea is Na4Fe 2.9 (PO4)2Mn 0.1 The theoretical amount of P2O7 generated is 2500ppm; the mixed slurry is coarsely ground and finely ground in sequence, the particle size of the grinding beads in the coarse grinding is 0.6μm, the rotation speed is 1500r / min, the time is 60min, and the particle size of the grinding beads in the fine grinding is 0.3μm, the rotation speed is 1800r / min, and the time is 160min, to obtain a grinding material with a median particle size D50 of 200nm; the grinding material is spray-dried, the inlet temperature is 205℃, and the outlet temperature is controlled at 90℃ to obtain a spray material; the spray material is crushed to obtain a crushed material with a median particle size D50 of 2.7μm; the crushed material is heated to 360℃ at a rate of 5℃ / min under a protective atmosphere, and the heat preservation time is 4h to obtain a sintered material;
[0103] 2) Mix the sintering material with glucose, wherein the amount of glucose added is Na4Fe 2.9 The theoretical amount of (PO4)2P2O7 produced is 7wt%, and the mixed material is coarsely ground and finely ground. The particle size of the grinding beads in the coarse grinding is 0.6μm, the rotation speed is 1500r / min, and the time is 60min. The particle size of the grinding beads in the fine grinding is 0.3μm, the rotation speed is 1800r / min, and the time is 160min, to obtain a mixed slurry with a median particle size D50 of 200nm; the above-mentioned mixed slurry is granulated by a spray dryer with an inlet temperature of 205℃ and an outlet temperature of 93℃ to obtain a spray material; the spray material is heated to 600℃ at a rate of 5℃ / min under a protective atmosphere, and the insulation time is 13h to obtain the positive electrode active material of this embodiment.
[0104] Example 2
[0105] The method for preparing the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), pyrrole is used instead of urea.
[0106] Example 3
[0107] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 1), polyacrylonitrile (weight average molecular weight is 2000) is used instead of urea.
[0108] Example 4
[0109] 1) adding a mixed raw material of sodium salt sodium pyrophosphate, iron salt iron oxide, phosphorus salt iron phosphate, manganese acetate and urea into deionized water to obtain a mixed slurry with a solid content of 25wt%, wherein the molar ratio of the Na element, Fe element, Mn element and P element in the mixed raw material is 4:2.7:0.3:4, and the amount of nitrogen added in urea accounts for 10% of Na4Fe 2.7 (PO4)2Mn 0.3 The mass percentage of the theoretical generated mass of P2O7 is 2000ppm; the mixed slurry is subjected to coarse grinding and fine grinding in sequence, the particle size of the grinding beads in the coarse grinding is 0.6μm, the rotation speed is 1700r / min, and the time is 80min, and the particle size of the grinding beads in the fine grinding is 0.3μm, the rotation speed is 2000r / min, and the time is 200min, to obtain a grinding material with a median particle size D50 of 150nm; the grinding material is spray-dried, the inlet temperature is 200℃, and the outlet temperature is controlled at 90℃ to obtain a spray material; the spray material is crushed to obtain a crushed material with a median particle size D50 of 2.7μm; the crushed material is heated to 400℃ at a rate of 5℃ / min under a protective atmosphere, and the heat preservation time is 4h to obtain a sintered material;
[0110] 2) Mix the sintering material with glucose, wherein the amount of glucose added is Na4Fe 2.7 The theoretical generated mass of (PO4)2P2O7 is 7wt%, and the mixed material is coarsely ground and finely ground. The particle size of the grinding beads in the coarse grinding is 0.8μm, the rotation speed is 1500r / min, and the time is 60min. The particle size of the grinding beads in the fine grinding is 0.3μm, the rotation speed is 1800r / min, and the time is 160min, to obtain a mixed slurry with a median particle size D50 of 250nm; the above-mentioned mixed slurry is granulated by a spray dryer with an inlet temperature of 200℃ and an outlet temperature of 90℃ to obtain a spray material; the spray material is heated to 500℃ at a rate of 5℃ / min under a protective atmosphere, and the insulation time is 16h to obtain the positive electrode active material of this embodiment.
[0111] Example 5
[0112] 1) adding a mixed raw material of sodium salt sodium pyrophosphate, iron salt iron oxide, phosphorus salt iron phosphate and urea into deionized water to obtain a mixed slurry with a solid content of 25wt%, wherein the molar ratio of the Na element, the Fe element and the P element in the mixed raw material is 4:3:4, and the mass percentage of the nitrogen added in the urea to the theoretical generated mass of Na4Fe3(PO4)2P2O7 is 3000ppm; the mixed slurry is coarsely ground and finely ground in sequence, the grinding bead particle size in the coarse grinding is 0.8μm, the rotation speed is 1400r / min, and the time is The grinding process is carried out for 30 minutes, the particle size of the grinding beads in the fine grinding is 0.4 μm, the rotation speed is 1600 r / min, the time is 120 minutes, and the grinding material with a median particle size D50 of 250 nm is obtained; the grinding material is spray-dried, the inlet temperature is 210°C, and the outlet temperature is controlled at 95°C to obtain a spray material; the spray material is crushed to obtain a crushed material with a median particle size D50 of 3.5 μm; the crushed material is heated to 200°C at a rate of 5°C / min under a protective atmosphere, and the heat preservation time is 6 hours to obtain a sintered material;
[0113] 2) Mix the sintering material with glucose, wherein the amount of glucose added is Na4Fe 2.7 The theoretical generated mass of (PO4)2P2O7 is 7wt%, and the mixed material is coarsely ground and finely ground. The particle size of the grinding beads in the coarse grinding is 0.8μm, the rotation speed is 1500r / min, and the time is 60min. The particle size of the grinding beads in the fine grinding is 0.3μm, the rotation speed is 1800r / min, and the time is 160min, to obtain a mixed slurry with a median particle size D50 of 250nm; the above-mentioned mixed slurry is granulated by a spray dryer with an inlet temperature of 210℃ and an outlet temperature of 95℃ to obtain a spray material; the spray material is heated to 700℃ at a rate of 5℃ / min under a protective atmosphere, and the insulation time is 10h to obtain the positive electrode active material of this embodiment.
[0114] Example 6
[0115] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the fine grinding time is adjusted to 360 min to obtain a grinding material with a median particle size D50 of 190 nm.
[0116] Example 7
[0117] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the fine grinding time is adjusted to 80 min, and the particle size of the grinding material is 500 nm.
[0118] Example 8
[0119] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 2), the temperature of the second sintering is adjusted to 700° C. and the time is adjusted to 16 h.
[0120] Example 9
[0121] The preparation method of the positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 1), the amount of urea added is Na4Fe 2.9 (PO4)2Mn 0.1 The theoretical production of P2O7 is 2250ppm.
[0122] Example 10
[0123] The preparation method of the positive electrode active material in this embodiment is basically the same as that in embodiment 1, except that in step 1), in step 2), the amount of glucose added is Na4Fe 2.9 (PO4)2Mn 0.1 9.9wt% of the theoretical amount of P2O7 produced.
[0124] Comparative Example 1
[0125] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that in step 1), the positive electrode active material is not coated with the first coating layer, that is, the mixed raw material does not contain urea.
[0126] Comparative Example 2
[0127] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that in step 2), the positive electrode active material is not coated with the second coating layer, that is, the mixed slurry does not contain glucose.
[0128] Comparative Example 3
[0129] A mixed raw material of sodium pyrophosphate, iron oxide, iron phosphate, urea, manganese acetate and glucose was added into deionized water to obtain a mixed slurry with a solid content of 25 wt%. The molar ratio of the Na element, Fe element, Mn element and P element in the mixed raw material was 4:2.9:0.1:4, and the amount of nitrogen added in the urea was Na4Fe 2.9 (PO4)2Mn 0.1 The theoretical amount of P2O7 generated is 2500ppm, and the amount of glucose added is Na4Fe 2.9The mixed slurry is coarsely ground and finely ground at one time, the grinding bead particle size in the coarse grinding is 0.6 μm, the rotation speed is 1500 r / min, the time is 60 min, and the grinding bead particle size in the fine grinding is 0.3 μm, the rotation speed is 1800 r / min, and the time is 160 min, to obtain a grinding material with a median particle size D50 of 200 nm; the grinding material is spray-dried, the inlet temperature is 205°C, and the outlet temperature is controlled at 90°C to obtain a spray material; the spray material is heated to 600°C at a rate of 5°C / min under a protective atmosphere, and the heat preservation time is 13h to obtain the positive electrode active material of this comparative example. Among them, the mass percentage of the coating layer in the positive electrode active material is 2.0wt%.
[0130] Comparative Example 4
[0131] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that in step 1), the sintering temperature is 410° C. and the holding time is 3 h.
[0132] Comparative Example 5
[0133] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that in step 2), the sintering temperature is 800° C. and the holding time is 9 h.
[0134] Comparative Example 6
[0135] The preparation method of the positive electrode active material in this comparative example is basically the same as that in Example 1, except that in step 1), the spray material is not spray-dried and crushed, and the mixed slurry after coarse grinding and fine grinding is directly dried and then subjected to the first sintering, while the other methods remain unchanged.
[0136] Test example
[0137] 1. The physical and chemical properties of the positive electrode active materials prepared in the above examples and comparative examples were characterized. The characterization results are shown in Table 1.
[0138] Table 1
[0139]
[0140]
[0141] 2. The positive electrode active materials prepared in Example 1 and Comparative Example 6 were subjected to SEM tests. The test results are shown in Figure 1 and Figure 2 .
[0142] Figure 1 is a SEM image of the positive electrode active material in Example 1, Figure 2is the SEM image of the positive electrode active material in Comparative Example 6, Figure 1 and Figure 2 It can be seen that compared with Comparative Example 6, the interior of the positive electrode active material particles in Example 1 is more compact and dense, with fewer pores; thus, it can be seen that the density of the positive electrode active material, that is, the porosity, can be effectively improved through crushing and the second granulation treatment, thereby achieving a higher powder compaction density.
[0143] 2. The positive electrode active materials in the above embodiments and comparative examples are made into sodium ion button batteries, comprising the following steps:
[0144] The positive electrode active material, conductive carbon black Super P, and polyvinylidene fluoride (PVDF) prepared above were mixed in a mass ratio of 9:0.5:0.5, and ground evenly in an agate mortar, and then an appropriate amount of N-methylpyrrolidone (NMP) solvent was added to prepare a uniform positive electrode active slurry, and then the slurry was evenly coated on a functional surface of the aluminum foil, and then transferred to a vacuum oven at 60°C for drying for 12 hours after baking at 110°C for 20 minutes; the dried electrode was cut into a circular electrode with a diameter of 13 mm using a button battery slicer, and the surface density was 1.25 g / 100 cm 2 , compacted density is 2.00g / cm 3 The positive electrode sheet of the battery was weighed and recorded, and the weighed electrode sheet was placed in a vacuum oven at 100°C for 12 hours for assembly of button half-cells. The battery was assembled in a closed glove box filled with argon. The assembly order was negative electrode shell-positive electrode sheet-diaphragm-sodium sheet-gasket-spring sheet-electrolyte-positive electrode shell. The assembled battery was placed on a battery packaging machine for compression packaging to obtain a CR2032 button battery; wherein the electrolyte included sodium hexafluorophosphate and an organic solvent, the concentration of sodium hexafluorophosphate in the electrolyte was 1M, and the organic solvent included methyl ethyl carbonate, diethyl carbonate, vinylene carbonate, propylene carbonate, 1,3-propane sultone and ethyl acetate in a volume ratio of 52.51:0.60:1.78:22.18:1.55:21.38. The battery was taken out of the glove box and allowed to stand for 24 hours before being subjected to electrochemical testing.
[0145] The impedance, first coulombic efficiency, rate performance and cycle performance of the button battery prepared above were tested:
[0146] 1) Impedance
[0147] The test was performed by the Autolab electrochemical workstation of Metrohm, Switzerland, with a test frequency range of 10 5 -10 - 2Hz, amplitude 10mV, the test data was fitted by Autolab software Nova 2.1, and the impedance value was calculated.
[0148] 2) First Coulombic efficiency
[0149] The button battery after standing was subjected to the first charge and discharge test, that is, charged at 0.05C for 1h, 0.1C for 1h, 0.2C to 3.4V, and then charged at 0.05C constant voltage, and the charging capacity was recorded; then discharged at 0.1C to 2.0V, and the discharge capacity was recorded; then the first coulomb efficiency (%) = (discharge capacity / charge capacity) × 100%.
[0150] 3) Rate performance
[0151] The button battery after the first charge and discharge is tested at a voltage range of 2.0V to 3.4V with 0.2C, 1C, 5C, and 10C cycles for 10 cycles each to obtain the discharge capacity after 0.2C cycle and the discharge capacity after 10C cycle. Then, 10C / 0.2C capacity retention rate (%) = (discharge capacity after 10C cycle / discharge capacity after 0.2C cycle) × 100%.
[0152] Figure 3 is the 10C / 0.2C capacity retention rate curve of the sodium ion battery in Examples 1 to 3 and Comparative Examples 1 and 2, Figure 3 It can be seen that compared with Comparative Examples 1 and 2, the sodium ion batteries in Examples 1 to 3 have higher rate performance.
[0153] 4) Cycle performance
[0154] After the first charge and discharge, the button battery is charged to 3.4V at 0.2C, and then discharged to 2.0V at 0.2C, and the charging capacity is recorded as C0; the button battery is cycled 100 times according to the above-mentioned charge and discharge mechanism, and the discharge capacity after the cycle is recorded as C1, then the cycle capacity retention rate (%) = (C1 / C0) × 100%.
[0155] The test results are shown in Table 2.
[0156] Table 2
[0157]
[0158]
[0159] From Table 2, we can see that:
[0160] Compared with Comparative Examples 1 to 6, the positive electrode active materials in Examples 1 to 10 have lower impedance, and the button cells including the positive electrode active materials in Examples 1 to 10 have higher first coulombic efficiency, rate performance and cycle performance; the impedance of the positive electrode active material in Example 3 is as low as 4.20×10 5 Ohm, accordingly, the 0.2C first coulombic efficiency of the button battery including the positive electrode active material is 91.3%, the 10C / 0.2C capacity retention rate is 87.5%, and the 1C cycle / 100 cycles capacity retention rate is 99.8%. It can be seen that the positive electrode active material in the present invention has high conductivity and small volume expansion during the charge and discharge process, which can effectively improve the cycle performance and rate performance of the battery.
[0161] 3. The sintered material prepared in the above Example 1 and the sintered material prepared in the comparative example 1 were subjected to Raman spectroscopy test. The test results are shown in Figure 4 .
[0162] Figure 4 is the Raman spectra of the sintered material in Example 1 and the sintered material in Comparative Example 1, Figure 4 In the figure, the “etched” curve corresponds to the sintered material prepared in Example 1, and the “original” curve corresponds to the sintered material prepared in Example 1. Figure 4 It can be seen that since the coating layer in Example 1 is doped with N element, compared with the coating layer not doped with N element in Comparative Example 1, the Raman curve G peak (1592cm -1 ) is shifted, which is caused by N doping.
[0163] 4. The positive electrode active material prepared in the above Example 1 was subjected to EDS test. The test results are shown in Figure 5 and Figure 6 .
[0164] Figure 5 is the EDS scan of the positive electrode active material in Example 1, Figure 6 This is a distribution diagram of the N element in the EDS scanning diagram of the positive electrode active material in Example 1. It can be seen that the N element doped in the coating layer on the surface of the positive electrode active material in Example 1 is distributed more evenly.
[0165] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material comprises secondary particles formed by agglomeration of primary particles; the primary particles comprise a matrix and a first coating layer coated on the surface of the matrix, and the surface of the secondary particles is coated with a second coating layer; The matrix includes a chemical composition of Na4Fe x (PO4)2M y P2O7 material; wherein 2.7≤x≤3, x+y=3; M includes at least one of Mn, Mg, Al, Cr, Ti, Co, Cu, Ni, K, and Li; The first coating layer includes a nitrogen-doped carbon material, and the second coating layer includes a carbon material.
2. The positive electrode active material according to claim 1, characterized in that The nitrogen-doped carbon material is obtained by sintering a carbon source including nitrogen element at a temperature of 200 to 400° C. for 4 to 6 hours.
3. The positive electrode active material according to claim 1 or 2, characterized in that: The porosity of the positive electrode active material is 10-15%, and / or the powder compaction density of the positive electrode active material is 1.9-2.2 g / cm 3 .
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The mass percentage of the first coating layer in the positive electrode active material is 0.8-1.0 wt %, and / or the mass percentage of the second coating layer is 1.2-1.6 wt %.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The average particle size of the primary particles is 0.4 to 1.0 μm, and / or the median particle size D50 of the secondary particles is 9 to 11 μm.
6. A method for preparing a positive electrode active material according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) subjecting raw materials including a sodium source, an iron source, a phosphorus source and a first carbon source to a first sand grinding process, a first granulation process, a crushing process and a first sintering process to obtain a sintered material, wherein the first sintering temperature is 200 to 400° C. and the holding time is 4 to 6 hours; wherein the first carbon source includes nitrogen; 2) subjecting the raw materials including the sintering material and the second carbon source to a second sand milling treatment and a second granulation treatment in sequence, and then subjecting the raw materials to a second sintering treatment to obtain a positive electrode active material; wherein the second sintering temperature is 500 to 700° C., and the heat preservation time is 10 to 16 hours.
7. The method for preparing a positive electrode active material according to claim 6, characterized in that: In step 1), the median particle size D50 of the raw material after the first sand milling treatment is 150 to 250 nm; And / or, in step 1), after the crushing treatment, a crushed material is obtained, and the median particle size D50 of the crushed material is 2.7 to 3.5 μm.
8. The method for preparing a positive electrode active material according to claim 6 or 7, characterized in that: The first sanding process and / or the second sanding process comprises coarse grinding and fine grinding of the raw material; The grinding beads in the coarse grinding have a particle size of 0.6 to 0.8 μm, a rotation speed of 1400 to 1700 r / min, and a time of 30 to 80 min; The particle size of the grinding beads in the fine grinding is 0.3-0.4 μm, the rotation speed is 1600-2000 r / min, and the time is 120-200 min.
9. A positive electrode sheet, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 5, or the positive electrode active material prepared by the preparation method according to any one of claims 6 to 8.
10. A sodium ion battery, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 5, or the positive electrode active material prepared by the preparation method according to any one of claims 6 to 8, or the positive electrode sheet according to claim 9.
Citation Information
Cited By
Titanium-doped high-density spherical nano sodium ferric pyrophosphate sodium ion battery positive electrode material and preparation method thereof
CN120184223A